The benefits of skin-to-skin contact in the postpartum period (Research, Society and Development, 2024)
Skin-to-Skin Contact (SSC) has emerged as a crucial practice for improving neonatal care. In this context, the aim of this study is to explore, through an integrative review, the benefits of skin-to-skin contact for both the health of the Newborn (NB) and the health of the mother in the postpartum period. Using the PICO strategy, articles were searched in the Google Scholar, BVS, SciELO, and PubMed databases, with descriptors such as "Postpartum period" and "Kangaroo method." Studies from the past eight years, in English and Portuguese, that clearly addressed the topic and were freely available were included. In the end, 21 articles were selected and analyzed. The results show that SSC offers various benefits for the mother-baby dyad, such as: facilitating the initiation and maintenance of breastfeeding; greater weight gain compared to controls in preterm newborns; better regulation of vital signs and sensory and emotional development of the newborn; reduction in the risk of neonatal infection, mortality, and length of stay in neonatal ICUs; strengthening of the emotional bonds between mother and child; for the mother, there is postpartum pain relief, a lower risk of postpartum hemorrhage and depression, as well as increased breast milk production. Therefore, it is clear that SSC is indispensable for the well-being of both the newborn and the mother. The implementation of this practice should be encouraged and ensured in hospital settings to maximize its positive effects.